2007
DOI: 10.1038/sj.bjc.6603559
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine chemoresistance and molecular markers associated with gemcitabine transport and metabolism in human pancreatic cancer cells

Abstract: To identify predictive molecular markers for gemcitabine resistance, we investigated changes in the expression of four genes associated with gemcitabine transport and metabolism during the development of acquired gemcitabine resistance of pancreatic cancer cell lines. The expression levels of human equilibrative nucleoside transporter-1 (hENT1), deoxycytidine kinase (dCK), RRM1, and RRM2 mRNA were analysed by real-time light cycler-PCR in various subclones during the development of acquired resistance to gemci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
231
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(242 citation statements)
references
References 23 publications
(21 reference statements)
7
231
1
Order By: Relevance
“…26 Nakano et al analyzed that the ratio of hENT1ÂdCK/RRM1ÂRRM2 expression decreased progressively with the development of acquired resistance in gemcitabine-resistant PC cell lines. 37 Nakahira et al reported that transfection of RRM1 siRNA resulted in >90% suppression of RRM1 messenger RNA (mRNA) and protein that was accompanied by a significantly reduced gemcitabine chemoresistance in human PC cell lines. Moreover, a clinical study with 18 recurrent PC patients treated by gemcitabine showed that patients with high RRM1 levels had diminished survival after …”
Section: Gemcitabine Transport and Metabolismmentioning
confidence: 99%
“…26 Nakano et al analyzed that the ratio of hENT1ÂdCK/RRM1ÂRRM2 expression decreased progressively with the development of acquired resistance in gemcitabine-resistant PC cell lines. 37 Nakahira et al reported that transfection of RRM1 siRNA resulted in >90% suppression of RRM1 messenger RNA (mRNA) and protein that was accompanied by a significantly reduced gemcitabine chemoresistance in human PC cell lines. Moreover, a clinical study with 18 recurrent PC patients treated by gemcitabine showed that patients with high RRM1 levels had diminished survival after …”
Section: Gemcitabine Transport and Metabolismmentioning
confidence: 99%
“…This results illustrated that expression ratio significantly correlated with gemcitabine sensitivity in eight pancreatic cancer cell lines, whereas no single gene expression level correlated with the sensitivity, indicating that the sensitivity of pancreatic cancer cells to gemcitabine is dependent on the ratio of four factors involved in gemcitabine transport and metabolism. On the one hand, the ratio of the four gene expression associated with acquired gemcitabine-resistance in pancreatic cancer cells (Nakano et al, 2007). Moreover, Duxbury et al, showed that small interfering RNA targeting RRM2 enhanced chemosensitivity to gemcitabine in pancreatic adenocarcinoma (Duxbury et al, 2004), suggesting its role as an attractive target for pancreatic cancer.…”
Section: Notementioning
confidence: 99%
“…Moreover, they identified RRM2 as a biomarker for the chemo-preventive effect of NS-398 in pancreatic cancer cells (Youns et al, 2011). Previous study illustrated that over-expression of RRM2 was associated with resistance to gemcitabine in pancreatic cancer (Nakano et al, 2007). In this study the expression level of RRM2 was analysed by q-PCR in different subclones during the development of acquired resistance to gemcitabine.…”
Section: Notementioning
confidence: 99%
“…However, the response ratio of PDAC to gemcitabine in clinical research is <25%, and those patients showing initial response generally develop drug resistance during therapy (6,7). The development of rapid resistance to gemcitabine may be due to either stem-like subpopulations of tumor cells, which have innate resistance to chemotherapy, or be caused by molecular changes in cancer cells, such as alternations of transport and metabolism of gemcitabine or the upregulation of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) or the DNA repair pathway (8)(9)(10)(11)(12). In addition to monotherapy, there are clinical treatments with gemcitabine in combination with other biological or chemotherapeutical targeted agents, such as the epidermal growth factor receptor (EGFR) inhibitors erlotinib, tipifarnib and gefitinib (13,14), but the combinations are limited, with unsatisfactory efficacy.…”
Section: Introductionmentioning
confidence: 99%